Optimalisasi Penyelesaian Sengketa Melalui Arbitrase Syariah: Pendekatan dan Tantangan dalam Praktik Hukum Indonesia - Ainun Nazib, Muhamad (Bayani, 2025)
Dispute resolution is an important aspect of the legal system that can affect social and economic stability. In Indonesia, sharia arbitration has emerged as an alternative dispute resolution that is in accordance with the principles of Islamic law. This journal aims to analyze the mechanism of sharia arbitration in resolving disputes and explore the advantages and challenges faced in its implementation. This study uses a qualitative research method with a descriptive research type. The methodology used includes literature studies and analysis of relevant cases. The results of the study indicate that sharia arbitration not only offers a fair and fast solution, but also pays attention to moral and ethical aspects in dispute resolution. However, there are several challenges, such as the lack of public understanding of sharia arbitration and integration with the national legal system. This study is expected to provide insight for legal practitioners and related parties to better understand and utilize sharia arbitration as a solution in dispute resolution.